THE EVOLUTION OF SUFI COMMUNITIES IN THE NORTH–EAST CAUCASUS IN XIX CENTURY - M. M. Magomedov (Гуманитарные и юридические исследования)
The paper analyzes the characteristics of Sufi ideology, which facilitates the perception of ideas gazavat during movement of mountaineers led by Shamil. Shows the relationship of the Sufis to the idea of ​​"holy war", it is proved that free societies are more willing to accept the idea of ​​Dagestan gazavat than communities under Khan's power are. Describes the transition followers of Sufi sheikhs from spiritual practices to the armed struggle. Considered the contradiction between Sufi communities opposing violent acts and communities to support the movement Muridism.